Strategies for Achieving National Gender Policy in Nigeira: A Critical Analysis. - Ekpe, Dickson E. (Advances in Social Sciences Research Journal, 2016)
Nigeria bid to pursue its international and local obligation of ensuring the realization of gender equality (Goal 3 of the millennium Goals), the Nigerian government replaced its women policy with a Gender policy in 2006. The policy goal is to eliminate cultural, religious gender based biases and harmful cultural and religious practices which reproduce inequalities in gender roles relations in the Nigerian society and thereby giving a subordinate status to women compared to men. However, development opportunities continue to elude women. The policy failed to challenge the structure which reproduces gender inequality and overall dis-empowerment of women. This paper sets to critically analyse the policy strategies of achieving the policy goal and objectives. We conclude and made recommendations as a guide to policy makers.